2021
DOI: 10.3390/app11188322
|View full text |Cite
|
Sign up to set email alerts
|

Thallium Use, Toxicity, and Detoxification Therapy: An Overview

Abstract: Thallium (Tl) is released into the environment, where is present at very low levels, from both natural and anthropogenic sources. Tl is considered as one of the most toxic heavy metals; it is a non-essential metal, present in low concentrations in humans. Tl toxicity causes dermatological and gastrointestinal diseases and disorders of the nervous system, and may even result in death. Many isotopes of Tl exist, with different uses. One of the isotopes of this metal (201Tl) is used in cardiovascular scintigraphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Thallium with preferential application in the industry [199,200] exerts a high degree of toxicity in humans [201][202][203] and animals [204]. This why thallium use in households has been forbidden in the US in 1965 and banned commercially in 1975 [199], a few countries subsequently also restricted its use [200].…”
Section: Thalliummentioning
confidence: 99%
See 2 more Smart Citations
“…Thallium with preferential application in the industry [199,200] exerts a high degree of toxicity in humans [201][202][203] and animals [204]. This why thallium use in households has been forbidden in the US in 1965 and banned commercially in 1975 [199], a few countries subsequently also restricted its use [200].…”
Section: Thalliummentioning
confidence: 99%
“…Thallium with preferential application in the industry [199,200] exerts a high degree of toxicity in humans [201][202][203] and animals [204]. This why thallium use in households has been forbidden in the US in 1965 and banned commercially in 1975 [199], a few countries subsequently also restricted its use [200]. Known as a historical environmental pollutant, thallium is found in the attic dust [109], while not analyzed in municipal solid waste landfills [68], but currently also detected in electronic waste [205], soil, water, and atmosphere [206], and a known contaminant in herbal medicine products [151] and edible plants [206].…”
Section: Thalliummentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the removal of these challenging task for the scientific community. In the past, many exp ical, and biochemical approaches have been used for the removal o termining the alteration of soil properties and disturbing the soil m diation is an eco-friendly, green, cheap, and safer technology that remove toxic and radioactive metals and organic pollutants (pestic lizers, and detergents) from the environment [92,93]. The results o al.…”
Section: Arsenic Phytoremediationmentioning
confidence: 99%
“…In the past, many expensive physical, chemical, and biochemical approaches have been used for the removal of arsenic from soil determining the alteration of soil properties and disturbing the soil microflora. Phytoremediation is an eco-friendly, green, cheap, and safer technology that makes use of plants to remove toxic and radioactive metals and organic pollutants (pesticides, herbicides, fertilizers, and detergents) from the environment [92,93]. The results obtained by Ahmad et al (2018) [94] at the Botanical Garten (University of the Punjab, Lahore) revealed that Eucalyptus camadulensis L., Terminalia arjuna L., and Salix tetrasperma L. can be used for arsenic phytoremediation.…”
Section: Arsenic Phytoremediationmentioning
confidence: 99%